Importance of parenteral iron sucrose therapy in correction of iron deficiency anemia during pregnancy - Shah, Aayushi B.; Shah, Parul T.; Patel, Rina V.; Patel, Shlok (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Iron deficiency anemia (IDA) is described as decrease in the hemoglobin and/or the amount of red blood cells in the blood due to iron insufficiency in the body. The aim of the study was to measure the efficacy and tolerability of iron sucrose in iron deficiency anemia in pregnant women. Methods: This was the prospective study of 50 pregnant women with iron deficiency anemia (Hb- 5 g/dl to 8 g/dl) between 20-34 weeks of gestation, who were given intravenous iron sucrose as per their requirements and follow up measurement of Hb was done. Results: Mean rise in Hb was seen by 2.2 g/dl. Minor side effects were seen in 6 out of 50 participants. Conclusions: Parenteral iron sucrose therapy can be used effectively and safely in pregnant women with iron deficiency anemia